ChemInform Abstract: Ln[N(SiMe3)2]3‐Catalyzed Cycloaddition of Terminal Alkynes to Azides Leading to 1, 5‐Disubstituted 1, 2, 3‐Triazoles: New Mechanistic Features. Issue 41 (19th September 2013) - Hong, Longcheng; Lin, Weijia; Zhang, Fangjun; Liu, Ruiting; Zhou, Xigeng
Abstract The first example of rare earth metal‐catalyzed cycloaddition of terminal alkynes (I) to azides (II) resulting in the formation of 1, 5‐disubstituted 1, 2, 3‐triazoles (III) is described.